PENGINTEGRASIAN NILAI-NILAI AGAMA ISLAM PADA PEMBELAJARAN DI SEKOLAH - Henrawansyah Harahap (Jurnal Literasiologi, 2021)
Integration according to Sanusi is a unified whole, not divided and scattered. Integration includes the needs or completeness of the members who form a unit with a close, harmonious and intimate relationship between the members of the unit. Whereas what is meant by value education integration is the process of integrating certain values into another concept so that it becomes a coherent and inseparable whole or the process of assimilation to become a unified whole and unified. In the world of education, the term integration is usually associated with a movement for democratic education that focuses on actual issues as the core curriculum. Integration learning centers on organizing important issues in the school curriculum with the wider world. This integration will connect problems with one another, so that a unity of knowledge is built. A knowledge that represents the parts to the whole (part whole relationships)